ТУРИСТИЧНЕ БРЕНДИНГУВАННЯ – ЯК ЗАСІБ РЕАЛІЗАЦІЇ СТРАТЕГІЧНИХ ЦІЛЕЙ РОЗВИТКУ КУРОРТУ ТРУСКАВЕЦЬ - Teodorovych, Larysa; Lushchyk, Mariia (Zhytomyr Ivan Franko State University, 2021)
This article describes the advantages and infrastructural features of the resort of Truskavets - the most developed spa resort in Ukraine. It is emphasized that this resort has a developed network of different types of accommodation: hotels, sanatoriums, boarding houses, villas, which have more than 26,550 beds. A wide range of medical and health services is provided. The marketing strategy of development of the city which includes formation of a tourist brand is developed. Based on the data of the SWOT-analysis, the operational goals and objectives for achieving the strategic goals of the resort development were determined. Comparing the goals and real changes, the achievements and problems of the resort were identified to achieve the strategic goal: "Truskavets is the capital of health. The leader among the balneological resorts of the world with the unique healing water Naftusya. Western Ukrainian Center for Medical and Cultural Tourism, Sports, Beauty and Longevity, with a developed infrastructure, high social and economic standards. " Many tasks have been affected by the Covid-19 pandemic, which has caused significant economic damage to the city. In addition, the development of the resort is hampered by negative factors related to the solution of issues at the legislative and administrative levels. The modern logo of Truskavets indicates that the uniqueness of the brand is based on water resources, but it does not fully represent the tourist and recreational potential of the city. In the minds of potential consumers, the city is perceived only as a place where you can improve your health. Mostly middle-aged and older people are interested in it, the city does not attract young people. In Truskavets, the range of services of the sanatorium-resort complex is expanding and the quality of service is improving. But, despite the developed system of accommodation facilities, the development of territorial tourist products is slow. The potential of the subregion and the surrounding centers of culture and tourism is not fully used. The material and technical base of Truskavets, in addition to medical and health tourism, allows to develop business, excursion, cultural and educational, entertainment, sports and other types of tourism.